PROFIL KEMAMPUAN LITERASI TEKNOLOGI PESERTA DIDIK SEKOLAH MENENGAH ATAS DI KOTA BANDUNG - Herni Yuniarti Suhendi (UIN Sunan Gunung Djati Bandung, 2017)
Technology in education is a primary need for every individual. The learning process in school was not spared from technology. So that teachers and learners need to understand and proficient in using technology, both during the learning process and in everyday life. So far, literacy skills in Indonesia is still very low. This is indicated by PISA data, in 2009 Indonesian students are ranked 57th with a score of 295 (The average score on OECD is 402), while in 2012 Indonesian students are ranked 64th with a score of 396 (The average score on OECD is 496). The Ministry of Education and Culture developed Gerakan Literasi Sekolah to support the need for the above problems. Based on these problems, this study aims to determine the extent of students' technological literacy profiles in the city of Bandung. The method used is giving questionnaires to students. With this research is expected to increase the ability of technology literacy in learning to support the needs of science in the future